Intrathoracic Gastric Volvulus presenting with GIT Bleed - Rahul Kadam; VSV Prasad (EL-Med-Pub, 2017)
Intrathoracic gastric volvulus in neonatal period is a life-threatening surgical emergency. We report a case of neonate with respiratory distress and GI bleeding who was diagnosed to have congenital diaphragmatic eventration with Intrathoracic gastric volvulus.